An Unusual Case of Pigmentation of Face and Hands - Sharif, Shawana; Haque, Anwar-Ul- (International Journal of Pathology, 2018)
Alkaptonuria is a rare metabolic disorder caused by deficiency of homogentisate dioxygenase; which leads to deposition of homogentisic acid which gets deposited in connective tissue as a melanin like pigment. We had a female patient who presented to us with abnormal pigmentation on her face and hands which was not cosmetically acceptable to her. Upon exploring, she had a history of darkening of urine. Her skin biopsy demonstrated fragmented collagen and deposits of pigment in connective tissue. Subsequently she was found to have high levels of homogentisic acid in urine. We recommend that every case of abnormal hyperpigmentation should be looked for the possibility of alkaptonuria